IMPLEMENTASI KEBIJAKAN DISIPLIN PNS DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR CAMAT UTAN, KABUPATEN SUMBAWA, PROVINSI NUSA TENGGARA BARAT - Rahmatin, Arihun (Institut Pemerintahan Dalam Negeri, 2018)
ABSTRACT The purpose of this study was to analyze the Discipline of Civil Servants policy in improving performance at the Utan Sub-District Office, Sumbawa Regency, West Nusa Tenggara Province. The research method used is a qualitative method, with a qualitative approach. Data obtained through data collection techniques: interviews and documentation. The results of this study indicate that the implementation of the disciplinary policy of Civil Servants in the Utan Sub-District Office, Sumbawa Regency basically has not run effectively. This is due to a lack of awareness to be able to work with discipline. Keywords: implementation, civil discipline policy, employee performance